Secondary lymphedema of limbs and chikungunya fever - Marques, Marcos Arêas (J Vasc Bras, 2019)
Certain systemic viral infections can be related to development of vascular complications, such as deep venous thrombosis and lymphedema of lower and upper limbs. These links have been well-established in patients with human immunodeficiency virus (HIV), hepatitis C, or influenza. Recently introduced into the American continent (2013), chikungunya virus is an arbovirus transmitted by mosquitoes of the Aedes genus and is the etiologic agent of chikungunya fever (CF), but its relationship to these vascular complications has not yet been consolidated. However, the CF outbreak that occurred during 2015 and 2016 resulted in the first cases described in the medical literature of acute and chronic vascular complications secondary to infection by this arbovirus. In this report, we describe the case of a patient who developed lymphedema of upper and lower limbs after an episode of CF.